2019
DOI: 10.3390/f10111040
|View full text |Cite
|
Sign up to set email alerts
|

Forest-Type Classification Using Time-Weighted Dynamic Time Warping Analysis in Mountain Areas: A Case Study in Southern China

Abstract: Efficient methodologies for mapping forest types in complicated mountain areas are essential for the implementation of sustainable forest management practices and monitoring. Existing solutions dedicated to forest-type mapping are primarily focused on supervised machine learning algorithms (MLAs) using remote sensing time-series images. However, MLAs are challenged by complex and problematic forest type compositions, lack of training data, loss of temporal data caused by clouds obscuration, and selection of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 63 publications
(93 reference statements)
0
18
1
1
Order By: Relevance
“…The calibrated PlanetScope data were then used to map cropping intensity information using the RF, ET, XGB, and TWDTW algorithms, with XGB being the most accurate and robust method, and TWDTW the least accurate method. Our results are different from the accuracy of TWDTW found in the studies of Belgiu and Csillik [2] and Cheng and Wang [44], where TWDTW produced better accuracy than the RF and SVM methods; although, accuracy results from our TWDTW analysis is still within the range of the accuracy reported in both these studies. However, our study is similar to the study conducted by Dadi [45], which reported higher accuracy from using RF than TWDTW for cropland mapping.…”
Section: Discussioncontrasting
confidence: 99%
“…The calibrated PlanetScope data were then used to map cropping intensity information using the RF, ET, XGB, and TWDTW algorithms, with XGB being the most accurate and robust method, and TWDTW the least accurate method. Our results are different from the accuracy of TWDTW found in the studies of Belgiu and Csillik [2] and Cheng and Wang [44], where TWDTW produced better accuracy than the RF and SVM methods; although, accuracy results from our TWDTW analysis is still within the range of the accuracy reported in both these studies. However, our study is similar to the study conducted by Dadi [45], which reported higher accuracy from using RF than TWDTW for cropland mapping.…”
Section: Discussioncontrasting
confidence: 99%
“…With constellation of two twin-satellites, Sentinel-2 has a very short revisit time, ideally providing land cover observations every 5 days under cloud-free conditions [10]. Such characteristics proved to be very useful when it comes to vegetation monitoring, with many studies specifically aiming at forest monitoring and inventory [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies proved that the use of time-series improves the tree species identification compared to using only single date satellite images [12,14,15]. This way, the species phenology can be exploited, but it also induces some new problems, such as increasing the dimensionality of the data and the requirements for more complex algorithms, and longer processing times [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Pasquarella et al (2018) combined spectral and temporal features obtained from Landsat time series images and were able to extract forest type information for the western portion of Massachusetts [6]. Grabska et al (2019) calculated temporal-spectral features and used them to retrieve information on various forest types, based on Sentinel-2 time series remote sensing images [7], while Cheng and Wang identified temporal patterns of different forest types and then combined them with spectral indexes and bands to identify forest types in Hunan, China, accurately and in detail [8]. Although these studies achieved forest type classification using spectral or temporal features at a local scale, these methods cannot be extended to large-scale forest type mapping owing to the limitations of remote sensing data acquisition, storage, and analysis capabilities [9,10].…”
Section: Introductionmentioning
confidence: 99%